1976
DOI: 10.1071/bt9760001
|View full text |Cite
|
Sign up to set email alerts
|

Studies on southern Australian taxa of Solieriaceae, Rhobdoniaceae and Rhodophyllidaceae (Rhodophyta)

Abstract: The morphology, reproduction, and relationships of the southern Australian species of three closely related families of the Gigartinales (Solieriaceae, Rhabdoniaceae and Rhodophyllidaceae) are described. In the multiaxial Solieriaceae, most genera of which are non-Australian, Solieria robusta (Greville) Kylin and five species of Callophycus Trevisan have been studied. Apart from Sarconema filiforme (Sonder) Kylin, these are the only southern Australian taxa retained in the family. In the uniaxial and non-proca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 0 publications
3
40
0
Order By: Relevance
“…The core reproductive characters that Kylin (1923Kylin ( , 1932Kylin ( , 1956) identified in Cystoclonium purpureum apply equally well to other genera in his Rhodophyllidaceae, as well as to some members of the Rhodophyllidaceae recognized by Schmitz & Hauptfleisch (1897) and those investigated by Min-Thein & Womersley (1976) in their treatment of the families Solieriaceae, Rhizophyllidaceae and Rhodophyllaceae from southern Australia. In most instances the auxiliary cell is an intercalary cell in an otherwise normal cortical filament.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The core reproductive characters that Kylin (1923Kylin ( , 1932Kylin ( , 1956) identified in Cystoclonium purpureum apply equally well to other genera in his Rhodophyllidaceae, as well as to some members of the Rhodophyllidaceae recognized by Schmitz & Hauptfleisch (1897) and those investigated by Min-Thein & Womersley (1976) in their treatment of the families Solieriaceae, Rhizophyllidaceae and Rhodophyllaceae from southern Australia. In most instances the auxiliary cell is an intercalary cell in an otherwise normal cortical filament.…”
Section: Discussionmentioning
confidence: 95%
“…Fredericq et al (1992) demonstrated that secondary gametophytic filaments unite with the supporting cell of the carpogonial branch directly below the auxiliary cell, but not with the gonimoblast filaments themselves, in Acanthococcus antarcticus. Secondary filaments are produced in the thallus interior to which sterile gonimoblast filaments later fuse in several species of Rhodophyllis (Min-Thein & Womersley, 1976;Thrainsson, 1986), and a small cluster of tightly packed secondary gametophytic filaments are formed towards the thallus interior in Craspedocarpus and Calliblepharis that are approached by basal sterile gonimoblast filaments that fuse with them (Min-Thein & Womersley, 1976;Thrainsson, 1986). Several non-procarpic genera have cystocarps in which the fusion cell extends throughout the length of a cortical filament almost to the central axis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Areschougia and Erythroclonium are currently also members of the Solieriaceae (Gabrielson and Hommersand 1982). Rhabdonia was at one time the type genus of the family Rhabdoniaceae (Kylin 1956, Min-Thein andWomersley 1976). It was transferred with the genera Areschougia, Erythroclonium, and Melanema from the Rhabdoniaceae (now Caulacanthaceae) to the family Solieriaceae on the basis of homologous reproductive structures and processes (Gabrielson and Hommersand 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Growth of gonimoblast filaments does not stop when open contact between ceils occurs and no new filaments bearing sporangia develop from the partially fused cells. The fusion of gonimoblast filament ceils with other ceils prior to carpospore formation is not unique to Clathromorphum, Melobesia and Mesophyllum but occurs in a diversity of other Rhodophyta, including members of the Acrotylaceae (Kraft, 1977a), the Dicranemaceae (Kraft, 1977b), the Mychodeaceae and Mychodeophyllaceae (Kraft, 1978), the Nizymeniaceae (Searles, 1968;Womersley, 1971), the Rhodophyllidaceae (Min-Thein & Womersley, 1976) and the Solieriaceae (Kraft, 1975;Min-Thein & Womersley, 1976). Because of this and because the carpospore bearing filaments emanate from the fusion cell, it is difficult to accept Lebednik's (1977, p. 391 Lebednik (1977) are procarpic with supporting cells functioning as auxiliary cells in a manner similar to that in Metamastophoraflabellata.…”
Section: As Dermatolithon)mentioning
confidence: 99%